If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 10 = 6x + -8 Reorder the terms: 10 + 3x = 6x + -8 Reorder the terms: 10 + 3x = -8 + 6x Solving 10 + 3x = -8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 10 + 3x + -6x = -8 + 6x + -6x Combine like terms: 3x + -6x = -3x 10 + -3x = -8 + 6x + -6x Combine like terms: 6x + -6x = 0 10 + -3x = -8 + 0 10 + -3x = -8 Add '-10' to each side of the equation. 10 + -10 + -3x = -8 + -10 Combine like terms: 10 + -10 = 0 0 + -3x = -8 + -10 -3x = -8 + -10 Combine like terms: -8 + -10 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| 4x-6(x+11)=-48 | | x^2+16x+16=4x-5 | | x+23,2/11=25 | | 6x+4y=13 | | -92=4+8x | | x+23[2/11]=25 | | 12+1/5m=20 | | 6t+5/9t-5=2t+7/3t-7 | | 6x+4(x-3)=13 | | 92x=883.2 | | 2X-6=3X+7 | | x=150+0.85(x) | | w-147.67=144.67 | | 3/5x21=3x | | .3333p+7=12-.6666p | | (2x^2)/(0.8-x^2)=53.3 | | 3/5+3=21x | | z/325=7 | | z/23=6 | | 1/9p=5/6 | | x=200+0.8(x) | | -5(X-4)+8X=6X-2 | | -6y-9=-3(y+9) | | x+65=50+75 | | 10/27=5/9t | | z^23=6 | | 18y-6=8y-70 | | 50+75=x+65 | | 5(X+4)/6=2X-5 | | 0.2x+1-2=0.5 | | x+(.01x)=15000 | | D=7/3(m-76) |